The Study of Philosophy and the Crisis of Meaning in Modern Education - Obienyem, Valentine (dialektika kontemporer, 2025)
This research offers a reflective and critical engagement with the meaning, enduring value, and contemporary status of philosophy. It explores the historical arc of philosophical inquiry, contrasting its classical vocation as the love of wisdom with its present-day fragmentation, marginalisation, and susceptibility to ideological drift. The paper interrogates both the internal tensions that have long animated philosophical discourse and the external disdain it often attracts in a technocratic and commercially-driven age. Drawing upon classical sources, historical episodes, and insights from modern philosophical voices, it examines the pedagogical diminishment of philosophy in formal education and the existential estrangement that has followed. Beyond mere critique, the essay advocates for a retrieval of philosophy’s authentic calling—not as arcane abstraction, but as a formative discipline that shapes the reflective, rational, and universal human being. In so doing, it affirms the irreplaceable role of philosophy in nourishing the interior life, sharpening moral clarity, and restoring coherence to the fractured modern mind.